The Linguistic Organization of the Visual Text in V. Kamensky’s “Concrete Poems”: An Intermedial Analysis of the Poem The Palace of S.I. Shchukin - Gik, Anna (Slavica, 2026)
The article is devoted to the analysis of the visual-poetic structure of Vasily Kamensky’s “concrete Poems,” based on the poem The palace of S.I. Shchukin. The study focuses on compositional principles, lexical-grammatical organization, and typographic features of the text within the aesthetic framework of Russian Cubo-Futurism. The application of an intermedial approach makes it possible to identify connections between poetic elements and works of painting from the collection of S.I. Shchukin. The poem is interpreted as a model of museum space, in which the text functions as a system of exhibition zones. The study reveals the dominance of the nominative principle, the reduction of verbal forms, and the synesthetic nature of imagery. It is demonstrated that typography performs a meaning-generating function, shaping the visual-spatial organization of the text.